Oriented Enterprise Architecture for Enhancing Digital Governance and Technopreneurship in Regional Governments - Rahmadani, Rizki Galang; Nurhayati, Oky Dwi; Nugraheni, Dinar Mutiara Kusumo (Aptisi Transactions On Technopreneurship (ATT), 2025)
This study examines disparities in the implementation of Indonesia’s Electronic-Based Government System (SPBE) which remain fragmented across regional governments and hinder efficient service delivery. The purpose of this research is to develop a hybrid enterprise architecture planning framework that combines TOGAF, Zachman, FEAF, and Gartner models to achieve more harmonized and interoperable SPBE adoption. A quantitative explanatory method was used with Partial Least Squares Structural Equation Modeling (PLS-SEM), involving data from 337 valid respondents across nine district and city governments in West Java Province. Four main constructs were examined, including SPBE implementation standardization, operational procedure clarity, technology harmonization, and institutional collaboration. The findings show that all constructs significantly improve digital governance effectiveness, with standardization being the strongest influencing factor with a coefficient value of 0.423 and significance level below 0.01. In addition to statistical validation, the study presents an operational framework containing procedural flow, logic matrix, and pseudocode that bridges theoretical concepts and practical implementation in SPBE planning. This hybrid framework provides a structured but also flexible approach suitable for Indonesia’s decentralized governance by enhancing interoperability, transparency, and coordination between agencies. Overall, the research contributes both theoretically and practically by demonstrating how the integration of enterprise architecture principles can strengthen SPBE implementation and support sustainable digital transformation within local governments.